Selective laser trabeculoplasty in treating post-trabeculectomy advanced primary open-angle glaucoma - ZHANG, HONGYANG (Exp Ther Med, 2016)
The aim of this study was to investigate the safety and efficacy of selective laser trabeculoplasty (SLT) treatment of patients with primary open-angle glaucoma (POAG) who could not obtain target intraocular pressure (IOP) through post-trabeculectomy medication. Sixteen patients with POAG (18 eyes), who could not obtain target IOP following medication and surgery, were treated with 360° SLT. The IOP, anterior chamber inflammation, and daytime and long-term IOP fluctuations before and 2 h, 1 day, 7 days, 1 month, 3 months, 6 months and 9 months after SLT were documented. SLT treatment success was defined as >20% IOP reduction compared with the baseline IOP at 6 and 9 months after the laser treatment date. Prior to SLT, the patients were administered different types (average, 2.8±0.8) of anti-glaucoma drugs and had an average IOP of 21.3±3.4 mmHg. Following SLT, the average IOP decreased to 16.2±3.0 mmHg and the success rate was 77.7%. The pre-SLT daytime IOP fluctuation was 4.1±1.4 mmHg, which decreased to 2.6±1.1 mmHg following the laser treatment (P<0.05). In conclusion, this study demonstrated that SLT could reduce the IOP in post-trabeculectomy patients with POAG, and reduce the daytime IOP fluctuations.